(untitled) (World Science, 2019)
Acne (acne vulgaris) is a long-term skin disease involving the hair follicles and oil glands. Nowadays the phytomedicines are preferable for acne treatment. The aim of this work is choosing of excipients for antiacne cosmetics with thyme oil. Thyme oil concentration was 0,25% for all compositions. Carbopol 940, Sodium carboxymethylcellulose, Hydroxyethylcellulose and PEG were chosen as the bases for gels with thyme oil. All formulations were examined by uniformity and pH tests. Franz diffusion dells were used for investigation of thyme oil releasing by the equilibrium dialysis method. It was established that Carbopol 940 had the highest value of thyme oil releasing from the gel composition.